Anthropogenic infrastructure as a component of urbogeosystems - Oleksii Chuiev (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
This article deals with the definition of the concept of "anthropogenic infrastructure" and attempts to find its place in the structure of urbogeosystems. The concept itself can not be called new, as many foreign authors have already used it, but the final definition never happened. The reasons why city studies are becoming more relevant in the face of ever-accelerating urbanization are briefly presented. Prerequisites for the emergence of the urban environment and approaches to its study are given. A special attention is paid to the consideration of urbosystems and their component structure. The main four components are described, which include the technosphere, biosphere, population and abiotic nature. The causes of the appearance of urban ecosystems and their specific features are analyzed. Based on the deficiencies of the "Urbosphere", "Urbosystem" and "Urboecosystem", the notion of "Urbogeosystem" is formed once again. Since architectural and construction objects are key components of such systems, their integration into anthropogenic infrastructure allows us to operate with a more general concept.